2022
DOI: 10.1186/s13690-022-00829-y
|View full text |Cite
|
Sign up to set email alerts
|

Do financial aspects affect care transitions in long-term care systems? A systematic review

Abstract: Background Suboptimal care transitions of older adults may ultimately lead to worse quality of care and increased costs for the health and social care systems. Currently, policies and financing often focus on care in specific settings only, and neglect quality of care during transitions between these settings. Therefore, appropriate financing mechanisms and improved care coordination are necessary for effective care transitions. This study aims to review all available evidence on financial aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…However, there remains a dearth of literature on how care coordination across healthcare and social services differs from coordination within the realm of healthcare alone [63]. Although none of the reviewed articles illustrated how financial incentives can specifically drive the quality of care coordination process in Singapore, many other studies beyond Singapore had illustrated that a pay-for-performance financial incentive structure paid to providers for a particular service dimension, i.e., care coordination, warrants further exploration [92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains a dearth of literature on how care coordination across healthcare and social services differs from coordination within the realm of healthcare alone [63]. Although none of the reviewed articles illustrated how financial incentives can specifically drive the quality of care coordination process in Singapore, many other studies beyond Singapore had illustrated that a pay-for-performance financial incentive structure paid to providers for a particular service dimension, i.e., care coordination, warrants further exploration [92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…We followed guidelines on scale development by DeVellis [25]. First (1), we developed a conceptual model based on Donabedian's quality framework and literature review carried out by Wieczorek and colleagues [4,6,15]. Second (2), we carried out a thorough process of item pool generation using deductive and inductive methods as recommended by DeVellis and Morgado [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…The search strategy was consulted with an academic health sciences librarian. The detail on the review methodology can be found in the published articles [4,6] and on the International Prospective Register of Systematic Reviews (PROSPERO) platform under identification number CRD42020162566. The review results were used to build on the item pool by identifying key core organizational and financial aspects that are relevant for care transition.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Through examination of short video campaigns on these platforms, in order to identify themes, messaging techniques, and types of videos used by KFC to engage their target audiences. Key Performance Indicators (KPIs), such as user engagement metrics and consumer feedback, will also be utilized as key performance metrics (KPIs) [12].…”
Section: Introductionmentioning
confidence: 99%